Addition of Endothelin A-Receptor Blockade Spoils the Beneficial Effect of Combined Renin-Angiotensin and Soluble Epoxide Hydrolase Inhibition: Studies on the Course of Chronic Kidney Disease in 5/6 Nephrectomized Ren-2 Transgenic Hypertensive Rats - Čertíková Chábová, Věra; Kujal, Petr; Vaňourková, Zdeňka; Škaroupková, Petra; Sadowski, Janusz; Kompanowska-Jezierska, Elzbieta; Tesař, Vladimír; Hammock, Bruce; Imig, John; Maxová, Hana; Červenka, Luděk; Vaněčková, Ivana (Kidney & blood pressure research, 2019)
INTRODUCTION: Previous studies in Ren-2 transgenic hypertensive rats (TGR) after 5/6 renal ablation (5/6 NX) have shown that besides pharmacological blockade of the renin-angiotensin system (RAS) also increasing kidney tissue epoxyeicosatrienoic acids (EET) levels by blocking soluble epoxide hydrolase (sEH), an enzyme responsible for degradation of EETs, and endothelin type A (ETA) receptor blockade retards chronic kidney disease (CKD) progression. This prompted us to evaluate if this progression will be alleviated by the addition of sEH inhibitor and ETA receptor antagonist to the standard complex blockade of RAS (angiotensin-converting enzyme inhibitor plus angiotensin II type 1 receptor blocker) in rats with established CKD. METHODS: The treatment regimens were initiated 6 weeks after 5/6 NX in TGR, and the follow-up period was 60 weeks. RESULTS: The addition of sEH inhibition to RAS blockade improved survival rate, further reduced albuminuria and renal glomerular and kidney tubulointerstitial injury, and attenuated the decline in creatinine clearance - all this as compared with 5/6 NX TGR treated with RAS blockade alone. Addition of ETA receptor antagonist to the combined RAS and sEH blockade not only offered no additional renoprotection but, surprisingly, also abolished the beneficial effects of adding sEH inhibitor to the RAS blockade. CONCLUSION: These data indicate that pharmacological strategies that combine the blockade of RAS and sEH could be a novel tool to combat the progression of CKD. Any attempts to further extend this therapeutic regimen should be made with extreme caution.
Keywords: Animals; epoxid hydrolasy; hypertenze; Endothelin A receptor blocker; Renal Insufficiency, Chronic; Receptor, Endothelin A; receptor endotelinu A; renin-angiotensin systém; Renin-Angiotensin System; Soluble epoxide hydrolase inhibitor; Nephrectomy; chronická renální insuficience; Renin-angiotensin system; Hypertension; Male; Chronic kidney disease; Rats, Transgenic; krysa rodu Rattus; mužské pohlaví; zvířata; Endothelin A Receptor Antagonists; antagonisté endotelinového receptoru A; 5/6 Renal mass reduction; Rats; potkani transgenní; nefrektomie; Epoxide Hydrolases